Evaluation of the dissemination of SNaX, a middle school-based obesity prevention intervention, within a large US school district. Issue 5 (12th February 2018) - Bogart, Laura M; Fu, Chong-Min; Eyraud, Jodi; Cowgill, Burton O; Hawes-Dawson, Jennifer; Uyeda, Kimberly; Klein, David J; Elliott, Marc N; Schuster, Mark A
Abstract: Few evidence-based school obesity-prevention programs are disseminated. We used community-based participatory research principles to disseminate an evidence-based middle-school obesity-prevention program, Students for Nutrition and eXercise (SNaX), to a large, primarily Latino, school district. In the 2014–2015 school year, we trained a district "champion" to provide training and technical assistance to schools and supplied print- and web-based materials (www.snaxinschools.org ). In one district region, 18 of 26 schools agreed to participate. We evaluated the dissemination process using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. All 18 schools implemented at least one SNaX component. Of 6, 410 students who attended an informational session, 1, 046 registered and 472 were selected to be Student Advocates, of whom 397 attended at least one meeting. Of 60 activities observed across schools, 77% were conducted with fidelity, but local resource constraints limited most activities to a relatively small number of Student Advocates (vs. the entire student body). Qualitative data from 46 school staff and 187 students indicated positive attitudes about the program. Teachers suggested that SNaX be implemented as part of the curriculum. In the 2015–2016 school year, 6 of the original schools continued to implement SNaX, and the champion trained 94 teachers from 57 schools districtwide. Cafeteria servings overall and fruit and vegetable servings, the primary outcomes, did not increase in SNaX schools versus matched-comparison schools. Our mixed-methods evaluation of SNaX showed acceptability and fidelity, but not effectiveness. Effectiveness may be improved by providing technical assistance to community stakeholders on how to tailor core intervention components while maintaining fidelity. Abstract : In this study of the dissemination of a middle-school obesity-prevention program, Students for Nutrition and eXercise (SNaX), we found high acceptability and feasibility, but did not find effects on school cafeteria food servings, possibly due to inconsistent implementation of key program components.